Evolution of quasistationary electron spectrum in open spherical quantum dot - Tkach, M.V.; Seti, Ju.O.; Voitsekhivska, O.M. (Condensed Matter Physics, 2008)
The evolution of electron quasistationary spectrum in open spherical quantum dot is under study within the
effective mass and rectangular potential model. Within the framework of the S-matrix model the exact solution
of Schr¨odinger equation is obtained in general analytical form. It is shown, for the rst time, that the generalized
resonance energies and widths introduced as the parameters de ning the probability distribution function (over
the energy or quasi momentum) of electron location in quantum dot, adequately characterize the evolution of
its quasistationary states (contrary to the S-matrix poles) in the whole range of barrier thickness: from zero
(free states) up to the in nity (stationary bound states are under the barrier and virtual and free states are
above it). Вивчається еволюцiя квазiстацiонарного спектру електрона у вiдкритiй сферичнiй квантовiй точцi. Розглядається модель однiєї ефективної маси та прямокутного потенцiала. Методом S-матрицi отримано точний розв’язок рiвняння Шредiнгера у загальному аналiтичному виглядi. Вперше показано, що узагальненi резонанснi енергiї та ширини введенi як параметри, що характеризують функцiю розподiлу (за енергiєю) ймовiрностi знаходження електрона в квантовiй точцi, адекватно (на вiдмiну вiд полюсiв S-матрицi) характеризують еволюцiю квазiстацiонарних станiв електрона на всьому iнтервалi змiни товщини бар’єра вiд нуля (вiльнi стани) i до безмежностi (стацiонарнi зв’язанi стани пiд бар’єром i вiртуальнi та вiльнi стани над бар’єром).